Patch containing lotus root fibers and preparation method thereof

The patch, which combines lotus root fiber with a hydrogel base, enhances mechanical properties through a mesh structure and collagen layer, solving the problems of patch displacement and tearing in laparoscopic hernia repair and improving postoperative recovery.

CN121668404APending Publication Date: 2026-03-17MESH TECHNOLOGY (BEIJING) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610152109.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-03
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing laparoscopic hernia repair patches are prone to displacement or tearing during postoperative movements due to increased abdominal pressure, and they also cause a strong foreign body sensation, affecting the recovery outcome.

Method used

The patch is made by fusing lotus root fibers with a hydrogel substrate, and is covered with collagen layers on both sides. A mesh structure is formed by laser perforation to enhance mechanical properties.

Benefits of technology

It improves the tensile, tear, and puncture resistance of the patch, prevents displacement and tearing, reduces foreign body sensation, enhances abdominal wall compliance, and increases the success rate of repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121668404A_ABST
    Figure CN121668404A_ABST
Patent Text Reader

Abstract

A patch containing lotus root fibers is formed by covering collagen layers on the two sides of a lotus root fiber hydrogel synthetic material, the lotus root fiber hydrogel synthetic material is obtained by fusing 20-40 parts by mass of lotus root fibers (3) and 60-80 parts by mass of a hydrogel substrate, and the prepared patch has excellent mechanical properties, and can be used as a patch for repairing the skin. The problem that the abdominal pressure of a patient is excessively increased due to cough, defecation and the like after an operation is effectively solved, displacement and tearing are prevented, and the repair success rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a medical biomaterial, and more particularly to a patch containing lotus root fiber and its preparation method. Background Technology

[0002] Surgical repair patches are synthetic materials that resemble "plastic mesh" in appearance. They are very thin and lightweight, and come in both absorbable and non-absorbable varieties. Because patches need to be implanted into the human body, they must minimize tissue reaction and possess a certain degree of toughness and flexibility to surgically repair tissue defects. Currently, there are many types of repair patches, which can be categorized into two main types based on their material: non-absorbable polypropylene and polytetrafluoroethylene patches, and absorbable bio-patch patches. Bio-patch patches are extracted from natural organisms using a series of complex technologies and can be understood as "cellular scaffolds."

[0003] For laparoscopic hernia repair surgery, patients may experience increased abdominal pressure after surgery, such as coughing or defecation. Such situations can significantly affect the recovery of the hernia and wound healing, potentially causing mesh displacement or a noticeable foreign body sensation, leading to discomfort, increased postoperative anxiety, and hindering postoperative recovery.

[0004] Chinese invention patent (CN116808315A) discloses a patch containing natural fibers, its preparation method, and its application. The patch comprises a porous structure consisting of a patch layer made of natural fibers and synthetic polymer materials; wherein the natural fibers include any one or a combination of at least two of bamboo fiber, hemp fiber, cotton fiber, or cellulose acetate. However, analysis of the patch's mechanical properties shows that it cannot meet the requirements for abdominal wall compliance during movements such as bending over. Summary of the Invention

[0005] To solve the above-mentioned technical problems, the present invention provides a patch containing lotus root fibers, which is formed by covering collagen layers on both sides of a lotus root fiber hydrogel synthetic material. The lotus root fiber hydrogel synthetic material is obtained by fusing 20-40 parts by weight of lotus root fibers with 60-80 parts by weight of a hydrogel substrate.

[0006] In a second aspect, the present invention also provides a method for preparing a patch containing lotus root fibers as described above, the method comprising the following steps:

[0007] S1: Lotus root fiber hydrogel synthetic material is obtained by fusing lotus root fiber in a grid pattern with a hydrogel substrate;

[0008] S2: The lotus root fiber hydrogel synthetic material is obtained by drilling circular holes in the lotus root fiber hydrogel synthetic material using a laser.

[0009] S3: Cover the perforated lotus root fiber hydrogel synthetic material with collagen membrane on both sides to form a collagen layer, and cut it into shape to obtain a patch containing lotus root fiber;

[0010] Thirdly, the present invention also provides the application of the patch containing lotus root fibers as described above in the preparation of hernia patches.

[0011] Compared with the prior art, the present invention has the following beneficial effects: The patch of the present invention is made by fusing lotus root fibers and hydrogel in a certain mass ratio, wherein the structural morphology of the lotus root fibers and the lotus root fiber hydrogel synthetic material is restricted, and then the two sides of the lotus root fiber hydrogel synthetic material are covered with a collagen membrane, which ultimately makes the patch have excellent mechanical properties. It effectively addresses the problem of transient increase in abdominal pressure caused by coughing and defecation after surgery, prevents displacement and tearing, and improves the success rate of repair. At the same time, the patch of the present application can cope with the deformation of the patient's abdomen, such as when bending over, its ability to conform to the movement of the abdominal wall is stronger, reducing the feeling of foreign body. Attached Figure Description

[0012] Figure 1 This is a schematic diagram of the preparation process of the present invention;

[0013] Figure 2 This is a schematic diagram of the overall structure of one embodiment of the lotus root fiber mesh of the present invention;

[0014] Figure 3 This is a schematic diagram of the overall structure of one embodiment of the lotus root fiber mesh of the present invention;

[0015] Figure 4 This is a schematic diagram of the overall structure of one embodiment of the lotus root fiber mesh of the present invention;

[0016] Figure 5 This is a schematic diagram of the layered structure of the patch of the present invention.

[0017] Figure labels: 1. Lotus root fiber hydrogel synthetic material, 2. Collagen layer, 3. Lotus root fiber, 4. Hydrogel substrate, 5. Circular pore. Detailed Implementation

[0018] The following embodiments further illustrate the content of the present invention, but should not be construed as limiting the present invention. Any modifications or substitutions made to the methods, steps, or conditions of the present invention without departing from the spirit and essence of the invention are within the scope of the present invention.

[0019] Although the present invention has been described in detail above with general descriptions, specific embodiments, and experiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

[0020] The preparation method of this application is used to prepare, such as Figures 2 to 5 Patches containing lotus root fibers.

[0021] In some embodiments, the patch containing lotus root fibers is formed by covering both sides of a collagen layer 2 with a lotus root fiber hydrogel synthetic material 1. The lotus root fiber hydrogel synthetic material 1 is obtained by fusing 20-40 parts by weight of lotus root fibers 3 with 60-80 parts by weight of a hydrogel substrate 4.

[0022] Based on the above embodiments, as a preferred embodiment, lotus root fibers 3 are arranged in a mesh pattern and then fused with a hydrosol substrate to obtain lotus root fiber hydrogel synthetic material 1, wherein the porosity of the lotus root fiber mesh is 50-60%;

[0023] Based on the above embodiments, as a preferred embodiment, the lotus root fiber hydrogel synthetic material 1 forms circular holes 5 with a diameter of 1-5 mm, and the gap between each circular hole 5 is 1-5 mm;

[0024] Based on the above embodiments, as a preferred embodiment, the thickness of the single-layer collagen layer 2 is 0.1-0.3 mm, and the thickness of the lotus root fiber hydrogel synthetic material 1 is 0.2-0.5 mm;

[0025] Studies have shown that the highest intra-abdominal pressure in humans is generated during coughing and jumping, reaching a peak of 171 mmHg. According to Laplace's law, converted to average tensile strength, the mesh must withstand a maximum theoretical tensile strength of 32 N / cm per unit width to successfully repair a hernia. The elasticity of the mesh is a key indicator of its physical properties and can be simulated by the area increase rate in a burst test. When the burst strength reaches 16 N / cm, the deformation range of the human abdominal wall is approximately 10%-30%. Mesh with elasticity values ​​below this range have poor adaptability to abdominal wall movements, causing patients to experience a noticeable foreign body sensation during bending, coughing, and other movements. Furthermore, the tear strength of the mesh determines the probability of hernia repair recurrence. Studies have shown that the tear strength of the human abdominal wall is approximately 20 N; meshes with tear strength below this value are prone to tearing, leading to hernia recurrence.

[0026] Tensile strength: Ensures the overall structural integrity of the patch and prevents breakage.

[0027] Tensile strength is the ability of a patch to resist axial tensile force, reflecting its ability to maintain structural integrity without breaking during daily activities (such as coughing and walking) or strenuous exercise;

[0028] Tear strength: Prevents localized tearing and avoids patch failure.

[0029] Tear strength is the ability of a patch to resist tearing forces, reflecting its ability to avoid local tearing during surgical procedures (such as cutting and fixing) or internal friction (such as tissue movement);

[0030] Bursting strength: resists localized protrusions and prevents perforation.

[0031] Bursting strength is the ability of a patch to resist pressure perpendicular to its surface, reflecting its ability to avoid perforation in the presence of protrusions within the body (such as tumor compression or tissue hyperplasia) or external impacts.

[0032] In some embodiments, see Figure 1 The process flow diagram of the preparation method of the above-mentioned patch containing lotus root fiber is shown in the figure.

[0033] The preparation method of the patch containing lotus root fibers includes the following steps:

[0034] S1: Using lotus root as raw material, extract lotus root fiber;

[0035] S2: Lotus root fiber hydrogel synthetic material is obtained by fusing lotus root fiber in a grid pattern with a hydrogel substrate;

[0036] S3: The lotus root fiber hydrogel synthetic material is obtained by drilling circular holes in the lotus root fiber hydrogel synthetic material using a laser.

[0037] S4: Cover the perforated lotus root fiber hydrogel synthetic material with collagen membrane on both sides to form a collagen layer, and cut it into shape to obtain a patch containing lotus root fiber.

[0038] Lotus root (Latin name: Nelumbo nucifera Gaertn.), also known as lotus root or jade lotus, is the rhizome of a plant in the lotus family (Nelumbo aceae). It is an aquatic vegetable, originally from India and later introduced to China. Because its underground stem is white, it is also called white stem.

[0039] Lotus root fiber is a new type of fiber independently developed in my country, following soybean protein fiber and bamboo fiber. It is made from lotus stems through processes such as soaking in river water, washing, drying, and degumming. The production principle utilizes the fermentation of microorganisms. After processing, lotus root fibers are light brown in color, 30-50 mm in length, and have a relatively stiff feel. Lotus root fiber not only has excellent moisture absorption, perspiration wicking, odor control, breathability, and anti-mildew and antibacterial properties, but also contains various trace elements beneficial to human health. Fabrics made from a blend of lotus root fiber and cotton fiber have a rough, simple, and natural style, similar to the unique style of Chinese handwoven fabrics, making them ideal for shirts and T-shirts. Furthermore, after atomization treatment, the fabric surface releases a unique, natural fragrance that is long-lasting.

[0040] In some embodiments, the method for extracting lotus root fibers can be...

[0041] (1) Raw material selection

[0042] Select fresh, disease-free lotus stems, wash and cut them into 2-3 cm sections;

[0043] (2) Microbial degumming

[0044] Place the cut stems in river / pond water (or fermentation liquid with a small amount of Bacillus subtilis) and soak for 7-10 days (water temperature 25-30℃). The principle is to use the fermentation of microorganisms (such as Bacillus subtilis) to decompose the pectin layer (the sticky substance that connects the fibers) in the stems, so that the fiber bundles can be separated naturally.

[0045] (3) Fiber extraction

[0046] Remove the degummed stems, rinse them with clean water, and gently peel off the fiber bundles by hand or machine.

[0047] (4) Drying and finishing

[0048] Drying: Unfold the fiber bundles and place them in a well-ventilated and dry place (or dry at a low temperature, ≤50℃) until the moisture content drops to below 8% (to prevent mold growth).

[0049] Finishing: Remove short fibers and impurities from the fibers by hand or by carding machine to make the fiber bundles neat.

[0050] Hydrogels are a type of highly hydrophilic three-dimensional network structure gel. They swell rapidly in water and can retain a large volume of water without dissolving in this swollen state. Due to the presence of a cross-linked network, hydrogels can swell and retain a large amount of water; the amount of water absorbed is closely related to the degree of cross-linking. The higher the degree of cross-linking, the lower the water absorption. This property is very similar to that of soft tissue. The water content in hydrogels can be as low as a few percent or as high as 99%. The aggregated state of a hydrogel is neither a completely solid nor a completely liquid. The behavior of a solid is that it can maintain a certain shape and volume under certain conditions, while the behavior of a liquid is that solutes can diffuse or permeate through the hydrogel.

[0051] Based on the above embodiments, as a preferred embodiment, the hydrogel in this application can be a polyvinyl alcohol (PVA) hydrogel. PVA hydrogels are mainly prepared by three types of crosslinking methods, namely chemical crosslinking, radiation crosslinking and physical crosslinking. Among them, the chemical crosslinking method uses chemical crosslinking agents such as aldehydes, epichlorohydrin, and boric acid to generate chemical crosslinking points between PVA molecules and crosslinking agent molecules to form a gel.

[0052] Radiation crosslinking mainly involves directly irradiating a PVA solution with gamma rays, ultraviolet rays, or electron beams, causing free radicals to be generated between PVA molecules, which then crosslink together to form a gel.

[0053] The physical crosslinking method mainly refers to the freeze-thaw cycle method. This method involves pouring the prepared PVA solution into a mold and leveling it, then freezing it in a refrigerator at -20℃ to -80℃ for a period of time, then taking it out and thawing it at room temperature for a period of time. This cycle can be repeated, and the number of freeze-thaw cycles can be adjusted according to the performance requirements of PVA. During the freeze-thaw process, microcrystalline regions will be formed inside the system as physical crosslinking points, thereby obtaining a three-dimensional network structure PVA hydrogel.

[0054] Based on the above embodiments, as a preferred embodiment, the hydrogel of this application may be purchased from Zhejiang Xingyue Biotechnology Co., Ltd.: its "Medical Silk Fiber Composite Gel" (Zhejiang Medical Device Registration Certificate No. 20252141196) is a Class III medical device.

[0055] Collagen membrane is a medical biomaterial membrane with collagen as its core component. The main component is collagen (accounting for about 80%-90%), supplemented with water (solvent), preservatives (such as formaldehyde), stabilizers (such as glycerin), etc. Some products add growth factors (such as EGF) to enhance the repair function.

[0056] Based on the above embodiments, as a preferred embodiment, the collagen membrane of this application may be purchased from Beijing Paisheng Biotechnology Co., Ltd.: its "Absorbable Biorepair Membrane" (National Medical Device Registration Certificate No. 20213171114) is a Class III medical device.

[0057] Porosity refers to the percentage of pore volume in a material to the total volume of the material in its natural state.

[0058] Based on the above embodiments, as a preferred embodiment, in step S1: fusing lotus root fibers in a grid pattern with a hydrogel substrate to obtain a lotus root fiber hydrogel synthetic material, 1-3 lotus root fibers are bundled together and twisted to a twist of 1000-2000 twists / m.

[0059] Based on the above embodiments, as a preferred embodiment, the twisted lotus root fibers are fixed in a grid pattern in a mold, the hydrogel is injected into the mold, and the mold is heated to 45-55°C in a water bath or constant temperature box for 1-3 hours. After polymerization, the material is removed from the mold, excess fibers are removed, and the lotus root fiber hydrogel synthetic material is obtained.

[0060] Based on the above embodiments, as a preferred embodiment, in step S1: fusing lotus root fibers with a hydrogel substrate to obtain a lotus root fiber hydrogel synthetic material, 20-40 parts by weight of lotus root fibers and 60-80 parts by weight of hydrogel substrate are fused to obtain the lotus root fiber hydrogel synthetic material, and the thickness of the lotus root fiber hydrogel synthetic material is 0.2-0.5 mm.

[0061] Based on the above embodiments, as a preferred embodiment, in step S1: fusing lotus root fibers with a hydrogel substrate to obtain a lotus root fiber hydrogel synthetic material, the lotus root fibers are arranged in a mesh pattern to form a lotus root fiber mesh, which is then fused with the hydrogel substrate, wherein the porosity of the lotus root fiber mesh is 50-60%;

[0062] Among them, lotus root fibers are bundled into bundles of 1-3 fibers and twisted to form a mesh pattern. The mesh can be rectangular, triangular, or diamond-shaped.

[0063] Based on the above embodiments, as a preferred embodiment, in step S2: obtaining the perforated lotus root fiber hydrogel synthetic material by laser drilling circular holes in the lotus root fiber hydrogel synthetic material, the diameter of the circular holes is 1-5 mm, and the gap between each circular hole is 1-5 mm.

[0064] Based on the above embodiments, as a preferred embodiment, in step S3: covering both sides of the perforated lotus root fiber hydrogel synthetic material with a collagen membrane to form a collagen layer, and cutting and shaping it to obtain a patch containing lotus root fibers, the thickness of the collagen membrane is 0.1-0.3 mm.

[0065] In some embodiments, the application of the above-mentioned patch containing lotus root fibers in the preparation of hernia patches is discussed.

[0066] Example 1

[0067] Materials needed: 40 g lotus root fiber, 60 g hydrogel, 0.1 mm thick collagen membrane;

[0068] S1: Twist 40g of lotus root fiber into a bundle with a twist of 1000 twists / m. Fix the twisted lotus root fiber in a grid pattern in a mold. The porosity of the lotus root fiber grid is 50%. Inject the hydrogel into the mold and heat it in a water bath or constant temperature box at 45℃ for 1 hour. After polymerization, remove it from the mold and remove excess fiber to obtain the lotus root fiber hydrogel synthetic material.

[0069] S2: The lotus root fiber hydrogel synthetic material is obtained by laser drilling circular holes to obtain a perforated lotus root fiber hydrogel synthetic material with a thickness of 0.2 mm, a diameter of 1 mm for the circular holes, and a gap of 1 mm between each circular hole.

[0070] S3: The perforated lotus root fiber hydrogel synthetic material is covered with a collagen membrane on both sides to form a collagen layer with a thickness of 0.1mm. The layer is then cut and shaped to obtain a patch containing lotus root fibers.

[0071] Examples 2-4

[0072] Examples 2-4 provide a method for preparing a patch containing lotus root fibers. This method includes all the steps of Example 1, wherein the lotus root fiber mesh is formed by arranging lotus root fibers in a grid pattern. The difference is that the parameters are shown in Table 1.

[0073] Table 1: Component dosage parameters in Examples 2-4 that differ from those in Example 1

[0074]

[0075] Examples 5-7

[0076] Examples 5-7 provide a method for preparing a patch containing lotus root fibers. This method includes all the steps of Example 3, except that in step S2: fusing lotus root fibers with a hydrogel substrate to obtain a lotus root fiber hydrogel synthetic material, the specific step parameters are as shown in Table 2.

[0077] Table 2: Steps and related parameters that differ from Example 3 in Examples 5-7

[0078]

[0079] Compare with Examples 1-3

[0080] The patch was prepared using the same preparation method as in Example 3, except that the lotus root fiber was replaced with silk fiber, bamboo fiber and cotton fiber respectively.

[0081] Compare with Example 4-8

[0082] The patch was prepared using the same preparation method as in Example 3, except that, as shown in Table 3, the parameters not shown in Table 3 are the same as in Example 3.

[0083] Table 3: Relevant parameters of Comparative Examples 4-8 that differ from Example 3

[0084]

[0085] Compare with Examples 9-10

[0086] The patch was prepared using the same preparation method as in Example 6, except that, as shown in Table 4, the parameters not shown in Table 4 are the same as in Example 6.

[0087] Table 4: Relevant parameters of Comparative Examples 9 and 10 that differ from Example 6

[0088]

[0089] Compare with Examples 11-20

[0090] The patch was prepared using the same preparation method as in Example 6, except that the lotus root fiber mesh was arranged in an irregular grid pattern.

[0091] Test Example 1 Performance Test

[0092] Patches prepared using the methods of Examples 1-7 and Comparative Examples 1-9 were used as test samples, and the following performance tests were conducted. All performance tests were performed three times, and the average value was taken:

[0093] (1) Tensile strength test

[0094] All test sample patches were cut into the same suitable size, with smooth edges, and qualified samples to be tested. The tensile testing machine was turned on, the parameters were set, and the tensile strength of all samples was tested. The data was statistically processed, and the results are shown in Table 5.

[0095] (2) Tear strength test

[0096] The trapezoidal tear strength method was used. All test samples were cut into isosceles trapezoids with a notch cut on the short side. The sample was clamped in the fixture of the tear strength tester. As the upper and lower fixtures separated, the notch cut on the short side of the sample was torn. The strength tester continuously recorded the force-displacement data of the test sample. Finally, the trapezoidal tear strength was calculated, and the results are shown in Table 5.

[0097] (3) Bursting force test

[0098] All test sample patches were clamped flat on the ring clamp of the bursting strength machine. The bursting strength machine was turned on and the pressure value was increased evenly under the test sample patch and pushed upward. The pressure value when the patch was burst was recorded. The results are shown in Table 5.

[0099] Table 5: Statistical table of test results for Examples 1-7 and Control Examples 1-9:

[0100]

[0101] Analysis of experimental results:

[0102] First, the relevant performance test results of Examples 1-7 show that the patches prepared by the preparation methods of Examples 1-7 have superior performance in terms of tensile strength, puncture resistance, and tear resistance. Furthermore, the preparation methods of Examples 1-7 enable the prepared patches to achieve a balanced state in various indicators, effectively addressing the problem of transient increases in abdominal pressure caused by coughing and defecation after surgery, and preventing displacement and tearing. Among them, the patches prepared by the preparation method of Example 6 are superior to the control examples 1-10 and other examples in various indicators.

[0103] Among them, Examples 5-7, compared with Example 3, adjusted the step parameters of "fusing lotus root fibers with the hydrogel substrate in a mesh pattern", specifically changing the polymerization temperature and time, thereby enhancing the tensile strength and tear strength. It can be seen that Examples 5-7 are superior to Examples 1-4 in terms of relevant performance, especially Example 6, which is superior to Examples 5 and 7. The comparison shows that adjusting the ratio of lotus root fibers to hydrogel, the amount and parameters of the twisting step of lotus root fibers, and the shape and distribution conditions of the lotus root fiber mesh all have a certain impact on the performance of the patch.

[0104] The test results of Comparative Examples 1-3 and Example 3 were compared. In Comparative Examples 1-3, lotus root fibers were replaced with silk fibers, bamboo fibers, and cotton fibers, respectively, while the remaining steps were the same as in Example 3. The comparison results showed that the tensile strength of Comparative Examples 1 and 2 was significantly increased. Although the bursting strength and tearing strength were similar to those of Examples 1-7, their tensile strength was much greater than 40 N / cm. This will directly lead to a decrease in tissue compatibility, such as foreign body reaction and scar hyperplasia. It is easy to cause displacement and recurrence. Combined with the preparation method of this application, it is impossible to meet the preparation requirements of the patch. The comparison shows that the type of fiber has a certain influence on the tensile strength performance of the patch.

[0105] Comparative Examples 4, 5, and 6 were based on Example 3, but with adjustments to the structural morphology of the lotus root fiber hydrogel synthetic material. The test results were compared. The tensile strength of Comparative Example 4 was improved, but the tear strength and burst strength were both reduced. All indicators were outside the standard range of this application. The tensile strength, tear strength, and burst strength of Comparative Examples 5 and 6 were all reduced. This shows that the structural morphology of the lotus root fiber hydrogel synthetic material can affect the tensile strength, tear strength, and burst strength of the patch.

[0106] Comparative Examples 7 and 8 were based on Example 3, with adjustments made to the raw material ratios, steps, and parameters of the lotus root fiber hydrogel synthetic material. The test results were compared, and the tensile strength and bursting strength of Comparative Examples 7 and 8 were significantly reduced, indicating that the adjustment of the raw material ratios, steps, and parameters of the lotus root fiber hydrogel synthetic material can affect the tensile and bursting properties of the patch.

[0107] Comparative Examples 9 and 10 adjusted the polymerization conditions of lotus root fiber web and hydrosol based on Example 6. The comparison showed that the tensile strength and tear strength of Comparative Example 9 were significantly reduced. Although the polymerization temperature of Comparative Example 10 was higher and the time was longer, although the bursting force met the standard, its tensile strength and tear strength were not significantly improved and still could not meet the various performance standards of the patch. The polymerization conditions of lotus root fiber web and hydrosol can affect tensile strength and tear strength.

[0108] Comparative Examples 11-21 adjusted the mesh arrangement of lotus root fibers based on Example 6. After comparison, it was found that the tensile strength, tear strength and bursting strength were unstable and the changes were irregular. In some comparative examples, one or two indicators were too high or too low, and only one comparative example met the standard.

[0109] In summary, the patches prepared by the methods of Examples 1-7 in this application have better performance indicators than those of Comparative Examples 1-10 in performance testing. Furthermore, the patch that meets the standard and solves the technical problem in this application is finally prepared by setting various conditions and parameters in a coordinated manner.

[0110] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A gauze-containing patch, characterized by, Formed by a lotus root fiber hydrogel synthetic material (1) double-sided covered collagen protein layer (2), the lotus root fiber hydrogel synthetic material (1) is obtained by fusing 20-40 mass parts of lotus root fiber (3) with 60-80 mass parts of hydrogel base (4).

2. The buta fiber-containing patch according to claim 1, characterized by, The lotus root fiber (3) is arranged in a grid type and fused with the hydrogel base to obtain the lotus root fiber hydrogel synthetic material (1), and the porosity of the lotus root fiber mesh is 50-60%.

3. The buta fiber-containing patch according to claim 1, characterized by, The lotus root fiber hydrogel synthetic material (1) forms circular holes (5) with a diameter of 1-5 mm, the gap between each circular hole (5) is 1-5 mm, the thickness of the single-layer collagen protein layer (2) is 0.1-0.3 mm, and the thickness of the lotus root fiber hydrogel synthetic material (1) is 0.2-0.5 mm.

4. A method of manufacturing a patch according to any one of claims 1 to 3, characterized in that, Comprising the following steps: S1: fusing the lotus root fiber arranged in a grid type with the hydrogel base to obtain the lotus root fiber hydrogel synthetic material; S2: punching the lotus root fiber hydrogel synthetic material by laser to obtain the punched lotus root fiber hydrogel synthetic material; S3: covering the punched lotus root fiber hydrogel synthetic material with collagen protein film on both sides to form a collagen protein layer, and cutting and forming to obtain the lotus root fiber-containing patch.

5. The preparation method according to claim 4, characterized in that, In the step S1 of fusing the lotus root fiber arranged in a grid type with the hydrogel base to obtain the lotus root fiber hydrogel synthetic material, 1-3 lotus root fibers are twisted as a bundle, and the twist degree is 1000-2000 twists / m.

6. The method of claim 4, wherein, In the step S1 of fusing the lotus root fiber with the hydrogel base to obtain the lotus root fiber hydrogel synthetic material, 20-40 mass parts of lotus root fiber and 60-80 mass parts of hydrogel base are fused to obtain the lotus root fiber hydrogel synthetic material, and the thickness of the lotus root fiber hydrogel synthetic material is 0.2-0.5 mm.

7. The preparation method according to claim 4, characterized in that, In the step S1 of fusing the lotus root fiber with the hydrogel base to obtain the lotus root fiber hydrogel synthetic material, the lotus root fiber is arranged in a grid type to form a lotus root fiber mesh, and then the lotus root fiber mesh is fused with the hydrogel base, wherein the porosity of the lotus root fiber mesh is 50-60%.

8. The method of claim 4, wherein, In the step S2 of punching the lotus root fiber hydrogel synthetic material by laser to obtain the punched lotus root fiber hydrogel synthetic material, the diameter of the circular hole is 1-5 mm, and the gap between each circular hole is 1-5 mm.

9. The method of claim 4, wherein, In the step S3 of covering the punched lotus root fiber hydrogel synthetic material with collagen protein film on both sides to form a collagen protein layer, and cutting and forming to obtain the lotus root fiber-containing patch, the thickness of the collagen protein film is 0.1-0.3 mm.

10. Use of the lotus root fiber-containing patch according to any one of claims 1-3 in the preparation of a hernia patch.

Citation Information

Patent Citations

  • Natural fiber-containing patch as well as preparation method and application thereof

    CN116808315A